2004
DOI: 10.1007/s00702-004-0160-9
|View full text |Cite
|
Sign up to set email alerts
|

Cu, Zn- and Mn-superoxide dismutase levels in brains of patients with schizophrenic psychosis

Abstract: Impaired oxidative stress defense has been reported in blood of both drug-naïve and antipsychotic-treated patients suffering from schizophrenic psychosis, indicating the involvement of free radical metabolism in the pathogenetic processes of schizophrenia. In this study, the concentrations of two isoenzymes of superoxide dismutase (SOD), Cu, Zn- and MnSOD, were determined with ELISA in various cortical (frontal, parietal, temporal and occipital cortex) and subcortical areas (putamen, caudate nucleus, thalamus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 43 publications
5
33
0
1
Order By: Relevance
“…Together, these findings indicate the presence of disturbed redox coupling mechanisms in schizophrenia, which may be related to GSH deficiency and/or time-related reductions in GSSG and GR activities (Yao et al, 2006a). Another post-mortem study examined a number of cortical and subcortical areas from donors with schizophrenia and controls, and found elevated levels of two SOD isoenzymes in the frontal cortex and substantia innominata of those with schizophrenia, thereby suggesting neuroanatomical specificity of redox disturbances in schizophrenia (Michel et al, 2004). Further supportive evidence is provided by a study reporting a 27 % reduction in the CSF glutathione level in neuroleptic-naive patients with schizophrenia compared with controls, which coexisted with a 52 % glutathione reduction in the medial prefrontal cortex, as measured by magnetic resonance spectroscopy (Do et al, 2000).…”
Section: Assays Of Oxidants and Antioxidantsmentioning
confidence: 90%
“…Together, these findings indicate the presence of disturbed redox coupling mechanisms in schizophrenia, which may be related to GSH deficiency and/or time-related reductions in GSSG and GR activities (Yao et al, 2006a). Another post-mortem study examined a number of cortical and subcortical areas from donors with schizophrenia and controls, and found elevated levels of two SOD isoenzymes in the frontal cortex and substantia innominata of those with schizophrenia, thereby suggesting neuroanatomical specificity of redox disturbances in schizophrenia (Michel et al, 2004). Further supportive evidence is provided by a study reporting a 27 % reduction in the CSF glutathione level in neuroleptic-naive patients with schizophrenia compared with controls, which coexisted with a 52 % glutathione reduction in the medial prefrontal cortex, as measured by magnetic resonance spectroscopy (Do et al, 2000).…”
Section: Assays Of Oxidants and Antioxidantsmentioning
confidence: 90%
“…Some illness-related abnormalities in RBCs may reflect equivalent abnormalities in the neurons, which are hard to examine in vivo [12, 22-29]. Because of its accessibility, the RBC membrane is commonly used as a “window” into the CNS.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…There is a lack of information on oxidative processes in cerebrospinal fluid and brain. It must be stressed that traces of oxidative damage may originate from various sources in the body and consequently, such a peripheral indicator may not necessarily reflect the conditions of the oxidative stress parameters in the brain [12]. Considering the size of the CNS in comparison to the other compartments of the human body, it seems reasonable to assume that changes in the levels of enzymes inside the brain can influence the enzyme plasma levels [21].…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Its biological importance, highlighted by its highly conserved nature, is supported by its crucial physiological and immunological functions. Interestingly, impaired oxidative stress defense, partly mediated by the ER stress proteins [Liu et al, 1998;Drake et al, 2002] has been reported in blood of both drug-naive and antipsychotic-treated patients suffering from schizophrenic psychosis [Michel et al, 2004]. The identified mutation in this study is located at a position conserved between human and mouse and creates a CpG site at the calreticulin gene core promoter sequence.…”
Section: Discussionmentioning
confidence: 92%